Exploring cost reduction approaches and associated challenges towards value for money for the Bangladesh Railway - Karim, Md. Rezaul (BARC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2016.